The Maximum Height and Attenuation of Impulse Waves Generated by Subaerial Landslides - Baoliang Wang; Lingkan Yao; Haixin Zhao; Cong Zhang (Shock and Vibration)
High-speed landslides that flow into reservoirs can cause impulsive water waves. To study the characteristics of the maximum impulse wave’s height and its attenuation, 25 sets of flume experiments were conducted using orthogonal theory and 6 main influencing factors were considered. Taking the impulse wave heights as the evaluation criteria and analyzing the 6 influencing factors at 5 different levels, the characteristics of the maximum impulse wave’s height and its attenuations were obtained. Then, statistical relationships between the maximum wave height and the controlling factors were proposed. Then, by combining the continuity equation and the hydrodynamic open channel transient flow movement equation, the process of landslide wave height attenuation was studied, and it was found that the attenuation of the wave is consistent with exponential attenuation. Then, combined with the data obtained from the orthogonal experiments, an attenuation equation for the surge was derived. Finally, the proposed equation was validated by applying it to the landslides that took place along the shore of the Zipingpu reservoir, which were triggered by the Wenchuan earthquake, and the results indicate that the calculated results are very close to the observed results.